Chopin and jazz. The case of Andrzej Jagodziński’s arrangement ofthe Prelude in E minor - Madeła, Patrycja (Interdisciplinary Studies in Musicology, 2018)
The current of jazz interpretations of Chopin’s music appeared in Polish jazz in the early 1990s. On the one hand, it is the most original and native stylistic trend of all trends influencing jazz in Poland. On the other, it is an exceptional phenomenon internationally, since no works of classical music have received so many jazz arrangements worldwide. The achievements of Polish jazz pianists in this regard have become most representative, since piano texture and the process of improvisation on a given theme show the most obvious references - not only musically, but also emotionally- to the musical language of Chopin. The recording of the award-winning album Chopin by the Andrzej Jagodziński Trio in December 1993 triggered a host of artistic arrangements of Chopin works by Polish jazz pianists, each of which constitutes an individual approach to the Chopin material, reflected in basic factors such as the criteria for the selection of compositions or themes and the process of the original’s transformation. Most jazz arrangements of Chopin’s music involve the piano miniatures that dominate the composer’s oeuvre. This is due to the clarity of the melodic lines, which inspire artists to turn them into themes for jazz standards. The Prelude in E minor, Op. 28 No. 4 has become the most frequently arranged piece of Chopin’s music in the field of jazz. The numerous arrangements are also stylistically diverse. Jagodziński’s arrangement is an example of this pattern being adapted for use in a jazz context. For him, the themes and mood of Chopin’s music have become a pretext for the creation of his own jazz compositions largely inspired by Chopin’s melodies and harmonies, but also by symmetrical form. Arrangements of Chopin’s music have been continually criticised by purists, who regard such procedures as a sort of profanation (any patriotic content in Chopin’s original compositions seems to vanish in the chaos of jazz improvisation, which disturbs the integral form of the originals). The basic problem here seems to be ignorance of the fact that Chopin’s music is essentially only a pretext, a kind of external emblem, for the creation of entirely new compositions, carrying different content, characterised by the author’s individuality.